2019
DOI: 10.1021/acs.iecr.9b00954
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient CO2 Capture from Flue Gas by Absorption with Amino Acids and Crystallization with a Bis-Iminoguanidine

Abstract: A hybrid solvent/solid-state approach to CO2 separation from flue gas is demonstrated based on absorption with aqueous amino acids (i.e., glycine, sarcosine), followed by crystallization of the bicarbonate salt of glyoxal-bis(iminoguanidine) (GBIG), and subsequent solid-state CO2 release from the bicarbonate crystals. In this process, the GBIG bicarbonate crystallization regenerates the amino acid sorbent, and the CO2 is subsequently released by mild heating of the GBIG bicarbonate crystals, which results in q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Instead, the carbonate salts were precipitated by reaction with Na 2 CO 3 , followed by quantitative CO 2 release from the carbonate solids and conversion into the free bases (Scheme 1). [20][21][22]27,28] and current work.…”
Section: Structure-solubility Relationships In Bigsmentioning
confidence: 97%
See 2 more Smart Citations
“…Instead, the carbonate salts were precipitated by reaction with Na 2 CO 3 , followed by quantitative CO 2 release from the carbonate solids and conversion into the free bases (Scheme 1). [20][21][22]27,28] and current work.…”
Section: Structure-solubility Relationships In Bigsmentioning
confidence: 97%
“…[24] BIGs are a class of anion-coordinating ligands readily accessible by imine condensation of dialdehydes with aminoguanidinium salts. [25][26][27][28][29] However, to date, only one crystalline BIG system, 2,6-pyridinebis(iminoguanidine), or Py-BIG, has been found effective for DAC. [20,21] The structurally analogous meta-benzenebis(iminoguanidine) (m-BBIG), although able to capture CO 2 from air, forms a poorly crystalline carbonate solid whose crystal structure has so far remained elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a nontoxic and environment friendly material, glycine has been reported to have a strong capability of converting CO 2 into anions in the solution through a zwitterionic mechanism. 58 , 60 In our experiments, aqueous solution of BTIG (6 mM, 5 mL) and aqueous solution of BTIG/glycine (6 mM/10 mM, 5 mL) were comparatively employed for direct CO 2 capture from air. The results of reaction kinetics are shown in Figure 2 c. For both systems, CO 2 could be efficiently captured from air, and the obtained weight of solid BTIG–CO 2 crystals increased as a function of standing time.…”
Section: Resultsmentioning
confidence: 99%
“…reported an innovative iminoguanidine type sorbent, namely 2,6-pyridine-bis(iminoguanidine) (PyBIG) which could capture CO 2 from ambient air, crystallize as an insoluble carbonate and regenerate PyBIG by mild heating with concomitant CO 2 releasing ( Seipp et al., 2017 ; Brethomé et al., 2018 ). Soon after, they disclosed another simple and robust iminoguanidine compound called glyoxal-bis(iminoguanidine) (GBIG), by which the flue gas CO 2 absorption led to the formation of a dehydrated bicarbonate salt ( Williams et al., 2019 ; Garrabrant et al., 2019 ); however, further results proved that the GBIG was ineffective for DAC ( Custelcean et al., 2020 ). In addition, their most recent structure-property relationship study of GBIG, MGBIG (methylglyoxal-bis(iminoguanidine)) and DABIG (diacetyl-bis(iminoguanidine)) revealed that minor modifications in the molecular structures would result in dramatic differences in the crystal structures, aqueous solubilities, conformational flexibilities, as well as free energies for CO 2 absorption ( Custelcean et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%